2015
DOI: 10.1371/journal.pone.0129687
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Oral Conditions and Quality of Life in Morbid Obese and Normal Weight Individuals: A Cross-Sectional Study

Abstract: The aim of this study was to identify the impact of oral disease on the quality of life of morbid obese and normal weight individuals. Cohort was composed of 100 morbid-obese and 50 normal-weight subjects. Dental caries, community periodontal index, gingival bleeding on probing (BOP), calculus, probing pocket depth, clinical attachment level, dental wear, stimulated salivary flow, and salivary pH were used to evaluate oral diseases. Socioeconomic and the oral impacts on daily performances (OIDP) questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
1
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 53 publications
6
31
1
16
Order By: Relevance
“…Lower salivary flow rates have been observed in people with obesity [4446] and it may be posited that this would diminish taste responses. However, other evidence indicates no difference in flow rates in people with and without obesity [47,48]. Both acute [17] and habitual [14] fat intake reportedly downregulate expression of NEFA receptors, which could reduce sensitivity, but evidence is based only on very preliminary data and, to be relevant, requires the unsubstantiated assumption that people with obesity necessarily select higher fat diets [21,49].…”
Section: Discussionmentioning
confidence: 99%
“…Lower salivary flow rates have been observed in people with obesity [4446] and it may be posited that this would diminish taste responses. However, other evidence indicates no difference in flow rates in people with and without obesity [47,48]. Both acute [17] and habitual [14] fat intake reportedly downregulate expression of NEFA receptors, which could reduce sensitivity, but evidence is based only on very preliminary data and, to be relevant, requires the unsubstantiated assumption that people with obesity necessarily select higher fat diets [21,49].…”
Section: Discussionmentioning
confidence: 99%
“…5 Pada populasi obesitas ditemukan hubungan dengan kondisi oral seperti penyakit periodontal, karies, dan xerostomia. 6 Hubungan obesitas dengan penyakit periodontal terjadi akibat adanya adiposa yang berlebih yang menyebabkan tingginya sitokin sehingga memicu periodontisis. 7,8 Saliva berperan penting sebagai homeostasis oral.…”
Section: Pendahuluanunclassified
“…In addition to its local impact on the periodontium and oral hygiene, periodontitis has a significant systemic effect. Previous reports have demonstrated that periodontitis is associated with obesity, diabetes, low birth weight, osteoarthritis, and cardiovascular disease 4,5 . In periodontitis treatment, the aim of the first phase is to eliminate the infectious source by removing plaque and calculus.…”
mentioning
confidence: 99%